Multiple risks analysis for aplastic anemia in Zhejiang, China: A case-control study. Issue 8 (February 2019) - Wu, Li-qiang; Shen, Ying-ying; Zhang, Ying; Kuang, Yue-min; Fang, Bing-mu; Wang, Zhou-zheng; Fu, Li-juan; Shao, Ke-ding; Shen, Jian-ping; Zhou, Yu-hong; Shen, Yi-ping; Ye, Bao-dong; et al.
Abstract : Abstract: To understand the risks associated with aplastic anemia (AA) in 4 cities of Zhejiang Province, China, with special focus on the joint contributions of multiple risks. Based on an Electronic Data Capture (EDC), a case control study was carried out. Data regarding socio-demographic, diseases history, living habits, and exposures to toxic substances, etc., were collected through survey questionnaires. t Test, chi-square test, or non-parametric rank sum test, and univariate and multivariate Logistic regression analysis were conducted to analyze data. The univariate logistic regression analysis results indicated that among all study participants (n = 1802), AA was associated with over 30 risks, in terms of their individual behaviors, daily and environmental exposures, diseases history, and family history. Multivariate logistic regression analysis further confirmed that the independent risks related to AA included presence of chemical factory within 3 km of living residence (odds ratio [OR] = 8.73, 95% CI: 1.42–53.74, P = .019), living in a newly decorated house/apartment (OR = 25.37, 95% CI: 4.44–144.81, P < .001), vegetarian diet (OR = 131.60, 95% CI: 3.45–5020.16, P = .009), preference of sugar (OR = 89.38, 95% CI: 7.22–1106.44, P < .001), preference of oily food (OR = 55.68, 95% CI: 5.12–605.26, P = .001), drinking lake water or pond water (OR = 58.05, 95% CI: 3.21–1049.81, P < .001), habit of staying up late (OR = 11.87, 95% CI: 3.43–41.02, P < .001), infection history (OR = 10.08, 95% CI: 2.75–36.93, P < .001). Result of receiver operating characteristic curve (ROC) analysis on the joint contribution of multiple risks indicated that AA was 13.835 times likely to occur when exposed to ≥1 risks than those exposed to 0 risks (95% CI: 9.995–19.149). Our study results demonstrated a comprehensive epidemiological pattern, in which the joint contributions of individual inherited health status, environment exposure, and individual behaviors lead to the occurrence of AA.